Migrações transnacionais e usos sociais da internet: identidades e cidadania na diáspora latino-americana - Brignol, Liliane Dutra (Universidade do Vale do Rio do Sinos, 2010)
The research aims to understand the dynamics of the social uses of the internet by Latin American migrants, in order to reflect on how identity issues cross uses of the world-wide web, demanding appropriations of their communication environments and setting strategies to access different conditions of citizenship. To do so, the concepts of identity, citizenship and social uses of the internet are discussed, through the approach to the multiple and complex Latin America landscape and to the contemporary transnational migrations dynamics. The investigation stems from the understanding that we live in a networked society, marked by a logic of non-hierarchical, flexible, interdependent, and organized interactions through the mediation of information technology and communication, which are studied in the survey in relation to the specificities of the migration phenomenon. For the empirical investigation of the social uses of the internet, it is made a methodological approach from an ethnographic perspective, which
Keywords: identidades; América Latina; cidadania; diáspora; migrações transnacionais; redes; internet - usos sociais; citizenship; diaspora; identity; latin america; networks; transnational migrations; internet - social uses; Ciências Sociais Aplicadas